Consumer Purchase Intention - Giovani Antania Hanjani; Arry Widodo (Jurnal Sekretaris dan Administrasi Bisnis, 2019)
Environmental issues are getting worse and worse. Indonesia is the second country to dispose of the largest marine waste in the world because the level of knowledge of the community regarding environmental impacts is still low. This study aims to determine how much influence the green brand on purchase intention mediated by green knowledge in Nestle Indonesia Company. The research method used is a quantitative method with the type of research used is descriptive verification and the measurement scale used is the Likert scale. The study population was all consumers of Nestle Indonesia’s product at Bandung City with a sample of 400 respondents. The sampling technique used in this study was nonprobability sampling. The data analysis method used in this study is Structural Equation Modeling (SEM). Data processing is done using SmartPLS. Based on the results of the hypothesis green brand of green knowledge has a value of 13,482 >α value of 1.649. It means that green brand variables have a positive and significant effect on green knowledge, and green brand on purchase intention has a value of 12,716 > tα 1.649 it means that green brand have a positive and significant effect on purchase intention, while green knowledge on purchase intention shows a value of 6,853 > tα value of 1,649 which means that green knowledge have a positive and significant effect on purchase intention. Based on the results of the study it can be concluded that the green brand in the good category, green knowledge in pretty good categories, purchase intention in the good categories, and the results of SEM analysis related the influence of green brand and green knowledge have a significant influence on purchase intention. Keywords: green brand, green knowledge, purchase intention